2019
DOI: 10.7150/ijms.33277
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adhesion prevention capabilities of the modified starch powder-based medical devices 4DryField® PH and Arista™ AH in the Optimized Peritoneal Adhesion Model

Abstract: Adhesion barriers can be based on numerous substances. In the rat Optimized Peritoneal Adhesion Model (OPAM) the starch-based hemostats 4DryField and Arista were tested for their capability to act in a preventive manner against adhesion formation (applied as a powder that was mixed in situ with saline solution to form a barrier gel). Adhesions were scored using the established scoring systems by Lauder and Hoffmann, as well as histopathologically using the score by Zühlke. Animals receiving saline solution wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 17 publications
4
18
0
Order By: Relevance
“…The calculated effect sizes show a medium to large effect for the reduction of the adhesion score and a large effect for the reduction of adhesion sites. The analyzed reduction of the adhesion score of 85% is in line with previously published results from experimental animal trials, where the product achieved reductions of the adhesion score ranging from 85 to 100% [29][30][31]. Previous evaluations were designed with second looks, but the patient collectives were smaller, and a retrospective protocol was used.…”
Section: Discussionsupporting
confidence: 82%
“…The calculated effect sizes show a medium to large effect for the reduction of the adhesion score and a large effect for the reduction of adhesion sites. The analyzed reduction of the adhesion score of 85% is in line with previously published results from experimental animal trials, where the product achieved reductions of the adhesion score ranging from 85 to 100% [29][30][31]. Previous evaluations were designed with second looks, but the patient collectives were smaller, and a retrospective protocol was used.…”
Section: Discussionsupporting
confidence: 82%
“…Not all have been studied in humans, and several involve animal model studies. However, comparing their anti-adhesion effectiveness, 4DryField seems to be the most effective [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of 4DryField ® PH and Arista on the formation of peritoneal adhesions were compared. It was found that only 4DryField ® PH was significantly effective (Poehnert et al 2019). The same model also showed the effect of the 4DryField ® PH in blocking the formation of adhesions into the intraperitoneal onlay meshes (IPOM) where adhesions are formed after hernia surgery and can cause serious medical complications (Winny et al 2016).…”
Section: Discussionmentioning
confidence: 99%